Photocatalytic degradation of dyes using synthesized δ-MnO2 nanostructures - Khatri, Manita; Gupta, Aakash; Gyawali, Kabita; Adhikari, Anup; Koirala, Agni Raj; Parajuli, Niranjan (Chemical Data Collections, 2022)
Nanostructures of manganese dioxide with unobjectionable properties can be employed to degrade organic waste. The polyol technique was used to create δ-MnO2 nanostructures (NSs), which were then characterized using X-ray diffraction (XRD), Fourier transformed infrared spectroscopy (FT-IR), Scanning electron microscopy (SEM), Transmission electron microscopy (TEM), and Ultraviolet-visible spectroscopy (UV–Vis). The Tauc plot predicted the band gap energy of various molar ratios as 3.02, 2.53, and 2.45 eV. The net charge and stability of δ-MnO2 were pH-dependent, influencing Congo red (CR) and Methylene blue (MB) dyes degradation efficiency. Moreover, various characteristic parameters viz; pH, time, and catalyst dosage on the degradation of dyes were also investigated, and more than 50% CR degradation was observed within 5 min. Photo-degradation study of dyes revealed that MB was degraded effectively at alkaline pH, unlike CR. However, reverse degradation was seen with CR on increasing the dose from 10 mg. [Display omitted]